Career Barriers Faced by Turkish Women Academics: Support for What? - (:unkn) unknown (DEOMED PUBL, ISTANBUL, 2018)
The purpose of this study was to investigate the barriers Turkish women academics working in state universities face throughout their career progression. The research was formed in qualitative research design. Data was collected through face-to-face interviews with a semi-structured interview form. 20 women academics in total including nine professors, one assistant professor, two doctors and eight instructors from a variety of disciplines participated in the research. Content analysis was conducted and the themes that emerged as a result of the data analysis were Support, Career Breaks, and Social Factors: Self-Confidence, Prejudice, and Role Conflict. The themes were supported by direct quotations from the participants' responses. Recommendations were made related to the findings of the research.
Keywords: Career; career barriers; higher education; women academics; GENDER-DIFFERENCES; HIGHER-EDUCATION; FAMILY CONFLICT; PROFESSORS; PREDICTORS; SCIENCE; WORK; MEN